A review of the rationales for corporate risk management: Fashion or the need? - Danijela Miloš Sprčić; Metka Tekavčič; Željko Šević (International Journal of Economic Sciences and Applied Research, 2008)
This paper presents the extensive literature survey based both on theoretical rationales for hedging as well as the empirical evidence that support the implications of the theory regarding the arguments for the corporate risk management relevance and its influence on the company's value. The survey of literature presented in this paper has revealed that there are two chief classes of rationales for corporate decision to hedge - maximisation of shareholder value or maximisation of managers' private utility. The paper concludes that, the total benefit of hedging is the combination of all these motives and, if the costs of using corporate risk management instruments are less than the benefits provided via the avenues mentioned in this paper, or any other benefit perceived by the market, then risk management is a shareholder-value enhancing activity.
Keywords: G32; G30; P31; 330; risk management; transitional economies; perception and management of risk; empirical Surveys